The Extent Implementation of Situational leadership styles and its relationship in achieving organizational efficiency Field study on Civilian Defense in Jordan - harahsheh, Faraj; ., . (International Journal of Engineering and Technology, 2019)
The aim of this paper is to know the extent implementation of situational leadership styles and its relationship in achieving organizational efficiency, field study on civilian defense in Jordan, the importance of study comes from the importance of situational leadership in achieving organizational efficiency, also civilian defense is considered one of the most important governmental emergency service, provides free services in the field of rescue ,ambulance, evacuation, to the community and state, whether in peace or war, the sample was (56) persons distributed for manager, assistant Director, head of department,(54) questioners returned,(2) questioners, disposed of,(52) questioners analyzed (93%)the study applied certain statistical techniques such as percentage, mean, standard deviation, simple correlation, Cornbach Alpha.The Results of the Study are: 1. Samples trends are positive with high degree toward (participant style, coaching style, directing style, delegation style) except authoritarianism style was weak.2. Samples trends are positive with high degree toward organizational efficiency.3. There is a significant relationship between situational leadership styles (participant style, coaching style, directing style, delegation style) and organizational efficiency, except authoritarianism style was weak. Recommendations The study came up with the following recommendations to the leaders and managers of civilian defense & organizations in public sector and private sector:1.Leaders and managers must increase interesting in situational leadership styles, because achieving goals depend on the decision-making in the suitable situation and time.2.Leaders and managers must know the capabilities, abilities, competences of the followers, and required needs such as training, development, needs and increased trust between the managers and followers to success situational leadership.3.Make other research regards to situational leadership styles and its relationship in achieving organizational effiencey in other organizations.